2013
DOI: 10.1007/s00408-013-9519-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Promoter 1082/−819/−592 Polymorphisms are Associated with Asthma Susceptibility in Asians and Atopic Asthma: A Meta-Analysis

Abstract: IL-10 promoter -1028A/G, -592A/C polymorphisms and their haplotypes, but not -819T/C polymorphism, correlate with asthma susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
4
35
1
Order By: Relevance
“…The results of previous meta-analyses exploring the association between these three polymorphisms in the IL-10 promoter region and asthma susceptibility are not consistent (Nie et al, 2012;Hyun et al, 2013;Zheng et al, 2014). Both Nie et al (2012) and Zheng et al (2014) concluded that the IL-10 -1082G/A and -592C/A (and not the -819C/ T) polymorphisms were significantly associated with asthma susceptibility.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of previous meta-analyses exploring the association between these three polymorphisms in the IL-10 promoter region and asthma susceptibility are not consistent (Nie et al, 2012;Hyun et al, 2013;Zheng et al, 2014). Both Nie et al (2012) and Zheng et al (2014) concluded that the IL-10 -1082G/A and -592C/A (and not the -819C/ T) polymorphisms were significantly associated with asthma susceptibility.…”
Section: Introductionmentioning
confidence: 91%
“…Both Nie et al (2012) and Zheng et al (2014) concluded that the IL-10 -1082G/A and -592C/A (and not the -819C/ T) polymorphisms were significantly associated with asthma susceptibility. However, the former did not analyze these relationships in children, and the latter reported no associations between these polymorphisms and pediatric asthma in an Asian population, despite stratifying the data by age.…”
Section: Introductionmentioning
confidence: 99%
“…Three dimorphic polymorphisms in the promoter region, at positions -1082 A/G (rs1800896), -819 T/C (rs1800871) and -592 A/C (rs1800872) have been identified in many diseases [12][13][14][15][16][17]. According to several previous studies, altered genetic make-up appears to be responsible with modulated levels of IL-10 [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that IL-10-1082A/G polymorphism was associated with various diseases such as Graves' disease, liver cirrhosis, ischemic stroke, deep venous thrombosis, and atopic asthma (Jin et al, 2014;Tang et al, 2014;Zheng et al, 2014;Guo et al, 2015;Liang et al, 2015). Zheng et al (2014) conducted a meta-analysis with 4,716 asthmatic patients and 5,093 controls, and reported that IL-10 promoter-1028A/G polymorphism was associated with susceptibility to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al (2014) conducted a meta-analysis with 4,716 asthmatic patients and 5,093 controls, and reported that IL-10 promoter-1028A/G polymorphism was associated with susceptibility to asthma. Tang et al (2014) conducted a case-control study on patients with deep venous thrombosis, and reported that IL-10-1082A/G polymorphism was correlated with the development of deep venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%